Review: Soil solarization and its effects on medicinal and aromatic plants - KHALID ALI KHALID (Smujo International, 2012)
Abstract. Khalid KA. 2012. Review: Soil solarization and its effects on medicinal and aromatic plants. Nusantara Bioscience 4: 36-44. Soil solarization or solar heating is a non-chemical disinfestation practice. Solarization effectively controls a wide range of soilborne pathogens, insects, and weeds. Soil solarization is based on the exploitation of solar energy for heating wet soil mulched with transparent plastic sheets to 40-55ºC in the upper soil layer. Thermal killing is the major factor involved in the pest control process, but chemical and biological mechanisms are also involved. The efficacy of the thermal killing is determined by the values of the maximum soil temperature and amount of heat accumulated (duration x temperature). The use of organic amendments (manure, crop residues) together with soil solarization (biofumigation) elevates the soil temperature by 1-3ºC, and improves pest control due to a generation and accumulation of toxic volatiles. Although cheaper than most chemicals used as soil fumigants, not all crops are worth the plastic prices, particularly in developing countries. Not all soilborne pests and weeds are sufficiently controlled. Cheaper and more environmentally accepted mulching technologies are needed before expanding the range of the controlled pests by solarization. Medicinal and aromatic plant production was affected by soil solarization.